Legal Politics of Space Utilization and Application of Sanctions Residential Areas in the Bima City Regional Spatial Plan - Mustamin; Ridwan; Zuhrah (Lembaga Bale Literasi, 2025)
This study examines the legal policy of spatial use for residential areas and the mechanisms for imposing sanctions in the Regional Regulation on the Regional Spatial Planning (RTRW) of Bima City. Using a descriptive analytical method with a normative juridical and sociological approach, the results show that the regulation of spatial use in residential areas has not been fully implemented optimally due to the high rate of land conversion and settlement expansion in disaster-prone zones. The application of administrative, criminal, and civil sanctions for spatial planning violations still faces institutional challenges, coordination, and consistent law enforcement. Therefore, strengthening control instruments, harmonizing regulations post-Job Creation Law, and increasing public legal awareness are needed to achieve orderly, sustainable spatial planning in Bima City.